Pelaksanaan Ijab Kabul Pernikahan di Masa Pandemi Covid-19 di KUA Kecamatan Sampang Madura - Chairah, Dakwatul (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2021)
This study aims to determine the implementation of the ijab kabul during the Covid-19 pandemic at the KUA, Sampang District, where there seems to be a change in the legal behavior of the community, where the Ijab and Kabul must be continuous and comply with health protocols. The method used is descriptive qualitative, which describes and studies in depth the practice of ijab and kabul at the KUA in Sampang District and then analyzes it based on the perspective of Islamic law or fiqh. This study found that, KUA Sampang District, Sampang Madura Regency issued a new procedure in the marriage contract. In the implementation of the Ijab and Kabul, the Penghulu as the representative of the female guardian performs ageppak bumih (clapping hands to the earth) after saying the Ijab so that the prospective groom immediately answers (kabul) the consent that was said by the Penghulu. They view that the marriage contract must be carried out in one assembly, where the ijab must be continuous with the kabul. In the implementation of the ijab kabul, the headmaster and the groom face each other, are about one meter apart, and do not shake hands. The penghulu claps his hands to the earth to remind the groom to immediately say Kabul, because there should be no time lag between ijab and kabul. This does not cause the marriage contract to be canceled, because ageppak bumih is an act of reminding the groom to immediately pronounce his kabul, answer the consent of the penghulu and so that the marriage contract remains valid. [Penelitian ini bertujuan mengetahui pelaksanaan ijab kabul pada masa pandemi Covid-19 di KUA Kecamatan Sampang yang nampaknya ada perubahan perilaku hukum masyarakat, di mana ijab dan kabul harus berkesinambungan serta mematuhi protokol kesehatan. Adapun metode yang digunakan, yaitu deskriptif kualitatif, yakni menjabarkan dan mempelajari secara mendalam praktik ijab dan kabul di KUA Kecamatan Sampang kemudian menganalisisnya berdasarkan perspektif hukum Islam atau fiqh. Penelitian ini menemukan bahwa, KUA Kecamatan Sampang Kabupaten Sampang Madura menerbitkan prosedur yang baru dalam akad nikah. Dalam pelaksanaan ijab dan kabul, penghulu sebagai wakil dari wali perempuan melakukan ageppak bumih (menepukkan tangan ke bumi) setelah mengucapkan ijab agar calon mempelai laki-laki segera menjawab (kabul) ijab yang diucapkan penghulu tersebut. Mereka memandang akad nikah harus dilaksanakan dalam satu majelis, di mana ijab harus berkesinambungan dengan kabul-nya. Dalam pelaksanaan ijab kabul, penghulu dan mempelai laki-laki saling berhadapan, berjarak sekitar satu meter, serta tidak berjabat tangan. Penghulu menepukkan tangan ke bumi bertujuan mengingatkan mempelai laki-laki untuk segera mengucapkan kabul, karena tidak boleh ada jeda waktu antara ijab dan kabul. Hal ini tidak menyebabkan batalnya akad nikah, karena ageppak bumih merupakan tindakan mengingatkan agar mempelai laki-laki segera mengucapkan kabulnya, menjawab ijab dari penghulu dan agar akad nikah tetap sah.]